Lack of interest cultivation: The impact of exam oriented education on Chinese school physical education - Tang Yao; Hasnol Noordin; Pathmanathan K.suppiah; Soon Singh Bikar Singh (Human Resource Management Academic Research Society, 2023)
Background: Despite the potential benefits of sports in promoting physical and mental health, many Chinese students exhibit a lack of interest and reluctance to do sports. Even after more than a decade of physical education experience, from primary school through university. Consequently, the physical fitness of Chinese college students has been declining. In response, the Chinese government has issued many official guidelines aimed at improving the physical fitness of teenagers through school sports programs. However, despite these efforts, the physical fitness of Chinese college students continues to decline annually, with increasing rates of obesity and myopia. Materials and Methods: This study was conducted at a college in southwest China, and participants were recruited through direct recruitment. A total of five sophomore volunteers participated in the study. Semi-structured interviews were employed to gain insights into their sports experiences from primary school to college. By analyzing their experiences, we aim to elucidate the reasons behind the persistent disinterest of Chinese students in sports despite more than a decade of physical education. Results: The teaching content of physical education in Chinese schools is monotonous and fails to engage students. Moreover, the teaching methods employed by physical education teachers lack variety and fail to elicit the enjoyment of sports activities during physical education classes. Conclusions: The current approach to physical education deprives students of the joy of sports, focusing predominantly on repetitive skills training and physical exercises. This approach contributes to students' aversion to physical education and gradual loss of interest in participating in sports.